2023
DOI: 10.1002/cctc.202300306
|View full text |Cite
|
Sign up to set email alerts
|

Selective Amination of Phenol to Cyclohexylamine over Metal‐Acid Bifunctional Catalysts Derived from Nickel Phyllosilicates

Abstract: Phenol amination to various valuable amines has attracted considerable attention in heterogeneous catalysis, but limited studies have focused on non-noble metal catalysts. This study reports a bifunctional catalyst (Ni/SiO 2 -AE) containing nickel nanoparticles and Lewis acid sites derived from nickel phyllosilicates for efficient amination of phenol to cyclohexylamine. The Ni/SiO 2 -AE catalyst resulted in 89.4% phenol conversion and 86.0% selectivity to cyclohexylamine at 160 °C for 2 h, which outperforms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Catalysts prepared via ammonia evaporation showed the highest activity and methane selectivity due to the ability to be activated at low temperatures. Liu 36 compared the performance of Ni/SiO 2 catalysts prepared via ammonia evaporation, deposition–precipitation and wetness-impregnation for selective amination of phenol to cyclohexylamine. The results indicated that Ni/SiO 2 catalysts prepared via different methods would lead to different Ni nanoparticle sizes and surface acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts prepared via ammonia evaporation showed the highest activity and methane selectivity due to the ability to be activated at low temperatures. Liu 36 compared the performance of Ni/SiO 2 catalysts prepared via ammonia evaporation, deposition–precipitation and wetness-impregnation for selective amination of phenol to cyclohexylamine. The results indicated that Ni/SiO 2 catalysts prepared via different methods would lead to different Ni nanoparticle sizes and surface acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [81] prepared a bifunctional Ni-based catalyst (Ni/SiO 2 -AE) containing nickel nanoparticles and Lewis acid sites derived from nickel phyllosilicates via a modified ammonia evaporation method and used it in the reductive amination reaction of phenol. As shown in Figure 4…”
Section: Ni-based Catalystsmentioning
confidence: 99%
“…[103]. Copyright 2018, Royal Society of Chemistry.Liu et al[81] prepared a bifunctional Ni-based catalyst (Ni/SiO2-AE) containing nickel nanoparticles and Lewis acid sites derived from nickel phyllosilicates via a modified ammonia evaporation method and used it in the reductive amination reaction of phenol. As shown in Figure4, the Ni/SiO2-AE catalyst enabled 89.4% phenol conversion and 86.0% selectivity for cyclohexylamine at 160 °C for 2 h, outperforming the catalysts formed via conventional deposition-precipitation (Ni/SiO2-DP) and wetness-impregnation (Ni/SiO2-WI).…”
mentioning
confidence: 99%